Eddy Arnold : pioneer of the Nashville sound - Streissguth, Michael (American made music series., 2009)
Fans of Arnold?s mellow music will appreciate the intensely detailed record of his private life and public career. Others may find the vivid picture of country music?s early decades (the many small-town radio stations and deejays that supported the music, the backroads tours, the struggling record labels) quite intriguing.?? Kirkus Reviews. Illustrated with fifty-four photographs and featuring a comprehensive discography and sessionography, this book traces Eddy Arnold?s origins from a cotton farm in western Tennessee to his legendary status in the world of country music. Michael Streissguth.